2022
DOI: 10.7554/elife.73933
|View full text |Cite
|
Sign up to set email alerts
|

A cellular and molecular atlas reveals the basis of chytrid development

Abstract: The chytrids (phylum Chytridiomycota) are a major fungal lineage of ecological and evolutionary importance. Despite their importance, many fundamental aspects of chytrid developmental and cell biology remain poorly understood. To address these knowledge gaps, we combined quantitative volume electron microscopy and comparative transcriptome profiling to create an ‘atlas’ of the cellular and molecular basis of the chytrid life cycle, using the model chytrid Rhizoclosmatium globosum. From our developmental atlas,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 91 publications
(118 reference statements)
0
11
0
Order By: Relevance
“…The biological mechanisms underpinning chemotaxis in aquatic chytrids are poorly understood (Laundon and Cunliffe 2021). It is possible that response to environmental signals could be linked to the rumposome, an enigmatic structure connecting the zoospore cell surface to the flagellar machinery that is present in R. globosum JEL800 zoospores (Laundon et al 2022) and is likely a site of calcium-mediated signalling (Powell 1983). Phototaxis has also been shown in chytrid zoospores, including with R. globosum JEL800, facilitated by a CyclOp-fusion protein based sensory system (Galindo et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The biological mechanisms underpinning chemotaxis in aquatic chytrids are poorly understood (Laundon and Cunliffe 2021). It is possible that response to environmental signals could be linked to the rumposome, an enigmatic structure connecting the zoospore cell surface to the flagellar machinery that is present in R. globosum JEL800 zoospores (Laundon et al 2022) and is likely a site of calcium-mediated signalling (Powell 1983). Phototaxis has also been shown in chytrid zoospores, including with R. globosum JEL800, facilitated by a CyclOp-fusion protein based sensory system (Galindo et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…encystment) is a possible trait that could facilitate the rapid colonisation and exploitation of ephemeral chitin-rich substrates such as mayfly exuviae in a dynamic resource-complex and competitive environment. Chytrid zoospore biology is poorly understood, including controls on the cell cycle (Medina and Buchler 2020, Laundon et al 2022), however based on frog mucus exposure experiments with B. dendrobatidis , likely involve critical host/substrate chemical cues that initiate encystment via calcium signalling and actin cytoskeleton remodelling (Robinson et al 2022). Chytrid zoospores are metabolically active, yet are transcriptionally and translationally inactive, with ribosomes held dormant (Medina and Buchler 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al . posited that the chytrid zoospore life stage is optimized for dispersal to new hosts rather than general metabolism [90]. The authors also reported complex lipid dynamics throughout the lifecycle of the chytrid, Rhizoclosmatium globosum .…”
Section: Discussionmentioning
confidence: 99%
“…Those of the large size fractions over‐express genes which may be likely involved in attached lifestyle during which they have to degrade the hosts' cell wall and hijack its lipid reserves (Gerphagnon et al, 2019). On the contrary, those of the small size fraction over‐express genes involved in glycolipids anabolisms, which have recently been described to take place during zoospore germination by Laundon et al (2022). Finally, some groups do not seem to be affected by size fraction such as saprotrophs for which neither taxonomic diversity nor metabolic potential variations are detected.…”
Section: Discussionmentioning
confidence: 99%